2022
DOI: 10.1287/orsc.2020.1397
|View full text |Cite
|
Sign up to set email alerts
|

CEO Power and Nonconforming Reference Group Selection

Abstract: Research shows that reference group selection underpins critical organizational processes, but less is known about publicly disclosed choices of reference groups, such as those for the evaluation of firm performance. Because audiences, such as investors and analysts, prefer reference groups created by independent entities they can trust, they disapprove of choices of custom peer groups created by reporting firms. Nevertheless, firms frequently choose reference groups that do not conform to audiences’ expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…We conjecture that firms will allocate more attention to their own experience than others’ experience when adapting their aspirations if these firms have CEOs whose personal interests (e.g., pay, power, or reputation) are more immediately based on how the focal firms perform relative to previous years than based on deviations from the industry norms, and CEOs that have relatively more discretion in departing from their own firms’ past actions than from the industry norms. A recent study by Audia, Rousseau, and Brion (in press) provides some initial evidence of this. Audia and colleagues found that, when forming their aspirations, firms led by powerful CEOs were more likely to use nonconforming reference groups that did not align with investors’ and analysts’ expectations.…”
Section: Discussionmentioning
confidence: 89%
“…We conjecture that firms will allocate more attention to their own experience than others’ experience when adapting their aspirations if these firms have CEOs whose personal interests (e.g., pay, power, or reputation) are more immediately based on how the focal firms perform relative to previous years than based on deviations from the industry norms, and CEOs that have relatively more discretion in departing from their own firms’ past actions than from the industry norms. A recent study by Audia, Rousseau, and Brion (in press) provides some initial evidence of this. Audia and colleagues found that, when forming their aspirations, firms led by powerful CEOs were more likely to use nonconforming reference groups that did not align with investors’ and analysts’ expectations.…”
Section: Discussionmentioning
confidence: 89%
“…The comparison with references, therefore, reflects a “diagnosis” or “self‐assessment” mechanism in which comparisons with similar references help a firm better assess its own abilities and standing in the market. Prior work conceptually mentions such self‐assessment mechanisms (Greve, 1998) as well as other purposes in association with reference selection (e.g., Audia et al, 2021; Porac et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Selecting a suitable comparison peer group is also an important issue in the BTOF (Audia et al, 2021). When we queried the compliance consultant about how her clients benchmarked waste levels, she noted that firms assess “…how they're doing compared to other companies in their same industry.…”
Section: Methodsmentioning
confidence: 99%
“…“Reappraisal of goals…appears to be a constant problem in an unstable environment” (Thompson & McEwen, 1958, p. 24) because it is difficult to make sense of and learn from a volatile environment. For example, volatility obfuscates the selection of an appropriate reference group and the observation of rival actions driving performance outcomes—a requirement for deriving social aspirations (Audia, Rousseau, & Brion, 2021).…”
Section: An Attention‐based View Of Aspiration Formationmentioning
confidence: 99%